Paracoccidioidomicose : estudo clínico-demográfico a partir de pacientes portadores de lesões bucais - Silva, Weuler dos Santos (2007)
The present work describes the demographic and clinic profile of 66 patients with oral lesions of paracoccidioidomycosis attended in a reference center for Oral Pathology, in the period between 1978 and 2006. There was predominance of middle-aged males, with large number of people with rural ocupation. In the oral cavity, most of the cases presented gingival lesions, followed by palate and lips. Very often, oral manifestations leaded to the diagnosis. Chronic multifocal form was predominant, with moderate systemic alterations. The low frequency of severe manifestations, in addition to the large number of patients without evident pulmonary alterations, was interpreted as evidence that oral lesions of paracoccidioidomycosis occur precociously. In addition, the high frequency of cases, as compared to previous works, suggests that the investigated area would be endemic to the mycosis. These hypotheses should be tested in future investigations.